Development of Jurisprudence Capability through the Science of Fundamentals of Jurisprudence for the researcher of Islamic knowledge: Bedayet Almujtahid as a case study - Ma’abdeh , Zainab Z. (Dirasat: Shari’a and Law Sciences, 2021)
This study addresses the topic of the development of jurisprudence capability through the science of fundamentals of jurisprudence for the researcher of Islamic knowledge, and the book “Bedayet Almujtahid” is presented in this study as a model in which Ibn Rushd reconstructs the issues of jurisprudence through the science of fundamentals of jurisprudence which would achieve a practical benefit represented in making the researcher’s Islamic knowledge of the jurisprudence based on understanding, not on conservation, on type , or on quantity. This study adopts the inductive and analytical method. The results showed that there is no way to get a full picture of the branches of Islamic jurisprudence except after getting the principles of Islamic jurisprudence and that the development of jurisprudence capability through this science would constitute controls that impede the mind of the researcher from getting lost in jurisprudence, because it takes care of the foundations, rules and right principles connected to the legal rulings extracted from their evidence. It also collects common principles and explains the reasons for the discrepancy between them, so it can differentiate between the correct judgment and the corrupted ones, so it does not deviate nor goes astray. It does not make its jurisprudence cause criticism, skepticism, and prolongation, which leads to weakening of the Islamic jurisprudence reputation.